Development of Android Application for Insect Animal Recognition Based on Augmented Reality as Interactive Learning Media - Paneo, Fahrezah R.; Manurung, Tohap K; Lapihu, Dodisutarma (MATICS: Jurnal Ilmu Komputer dan Teknologi Informasi (Journal of Computer Science and Information Technology), 2024)
This study aims to develop Augmented reality applications as an interesting and interactive learning media and able to provide convenience in introducing insect animals into 3-dimensional form. The method used to design this system is the Prototype method and application testing is used Usability testing. Based on the results of development and testing, the majority of respondents indicated that the Insect World application functions well and is easy to use. Positive responses are also seen in the perception of learning about insect animals provided by the Insect World application. The appearance of the application and the real insect models displayed are also favored by the majority of respondents, and most like the learning experience using the Insect World Augmented reality application.